2003
DOI: 10.1002/ajmg.a.20601
|View full text |Cite
|
Sign up to set email alerts
|

Slow progression of ataxia‐telangiectasia with double missense and in frame splice mutations

Abstract: Ataxia-telangiectasia (A-T) is caused by mutations of the ATM gene, the product of which is involved in the regulation of cellular responses to radiation damage. Ataxia usually starts in early childhood but a delayed age at onset and slower rate of neurological deterioration has been found for some patients with variant A-T. Only few patients have been documented to survive into the 4th decade. We report on a patient with an attenuated form of A-T who was diagnosed as having A-T by the age of 52 years and died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 36 publications
(49 reference statements)
2
36
0
2
Order By: Relevance
“…2,3 Examples of survival past the fifth decade exist in rare case studies. 4 Recent studies demonstrate the strong correlation between ATM kinase activity and phenotypic severity across the AT disease spectrum. 3 Patients with classical AT, possessing biallelic null ATM mutations, present in early infancy with a progressive and debilitating cerebellar ataxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Examples of survival past the fifth decade exist in rare case studies. 4 Recent studies demonstrate the strong correlation between ATM kinase activity and phenotypic severity across the AT disease spectrum. 3 Patients with classical AT, possessing biallelic null ATM mutations, present in early infancy with a progressive and debilitating cerebellar ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Life expectancy is reduced to the mid-20s due to respiratory failure and malignancy (primarily hematologic). 4 …”
Section: Discussionmentioning
confidence: 99%
“…Given the advanced age of the patient, the increased baseline G2/ GF ratio could indicate the accumulation of cells with agerelated DNA damage [37]. On the other hand, slow progression of the disease has been reported in older ATpatients with mild clinical course due to double missense or in frame splicing mutations of the ATM gene [10,39]. Another potential candidate for such "mild" ATM mutations in our series presented with G2/GF cell fractions that consistently were at the upper limit of non-AT controls regardless of whether his PBLs were tested after a radiation dose of 1.5, 4, 6 or 8 Gy (see Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Patients with a less severe phenotype and (mostly) later onset of symptoms carry (less severe) mutations that preserve residual ATM protein function [10,22,39].…”
Section: Introductionmentioning
confidence: 99%
“…27 Later, it was shown that missense mutations predominate in breast cancer populations, 28 and that some missense mutations lead to mild, almost clinically undetectable, A-T in compound heterozygotes. 29,30 Thus, the crucial next step is determining which wolframin missense mutations predispose heterozygous carriers to psychiatric disorders. The population-based application of the index-test method 11 can do this with high statistical power and unassailable rigor.…”
Section: Discussionmentioning
confidence: 99%